Nasal packing, periorbital edema and ecchymosis after septorhinoplasty - Sadegh, Shahin Mohammad; Motamed, Sadrollah; Tarahom, Mohammadreza; Baghaei, Mohammad; Otaghvar, Hamidreza Alizadeh (Researcher Bulletin of Medical Sciences, 2018)
Introduction:Edema and ecchymosis after septorhinoplasty is an unpleasant manifestation for both the patient and surgeon. Although routine nasal packing is frequently done after septorhinoplasty, assessing the relevancy of post-surgical periorbital edema and ecchymosis with nasal packing eventually may helps to clarifying more prohibitable causes of these complications that are unintentionally perform. Materials and Methods: In an interval of 1.5 years, 124 patients whom were candidates of septorhinoplasty by one surgeon in a center of plastic and reconstructive surgery in Tehran participated in our study. Patients were randomly divided in two groups. For half of them at the end of operation bilateral routine nasal packing was done and for the rest a light dressing limited to the nostril was performed. Thereafter, sequentially in the 1st, 3rd, 7th and 30th postoperative day severity of periorbital edema and ecchymosis were recorded based on a scaling system by a third person who was not informed about the study. Results: Conventional nasal packing is relevant to an increasing number of cases with periorbital edema and ecchymosis after septorhinoplasty. The difference between patients whom were nasally packed or not was not significant at the first postoperative day but in the 3rd and 7th day it was meaningfully less in number and severity in the unpacked group. Discussion: This shows that it is not necessary to do pack in every patient after septorhinoplasty and performing a light dressing may suffice.